DAILY ACTIVITY IN DIGITAL STORYTELLING TO IMPROVE SPEAKING SKILL IN SECONDARY SCHOOL - Sari, RAD Permata Puspita; Dian Arief Pradana; Mochammad Ardi Setyawan; Abd. Rahman (Esteem Journal of English Education Study Programme, 2025)
Speaking is a vital yet challenging skill for EFL students, especially in secondary schools, due to limited practice, low confidence, and classroom anxiety. Traditional teacher-centered methods often fail to offer meaningful speaking opportunities. This study, conducted at SMK Sritanjung Banyuwangi using a qualitative descriptive method, explores how Digital Storytelling (DST) based on students’ daily routines can enhance speaking skills, motivation, engagement, and digital literacy. Six tenth-grade students created English video blogs (vlogs) about their daily activities. Data were collected through speaking assessments, open-ended questionnaires, observations, and documentation, then analyzed using Miles and Huberman’s interactive model. The results showed notable improvements in pronunciation, fluency, grammar, and vocabulary. DST also boosted students’ creativity, confidence, and motivation while reducing anxiety. Despite initial nervousness and technical challenges, students responded positively, finding DST enjoyable and supportive. Overall, DST provided an engaging, low-pressure environment that encouraged autonomous learning and effective communication.